Aux origines des nationalismes balkaniques La Révolution française et le Sud-Est de l'Europe - Kitromilidès, Pascal M. (Mondes méditerranéens et balkaniques (MMB), 2021)
As we commemorate the Bicentennial of the Greek Revolution, this study by Pascal Kitromilidès of the reception of the French Revolution and the influence it had on the birth of nationalism in the Balkans is timely. The 1990 Greek edition was very much in tune with the events of the day, from the 1989 commemorations to mark the Bicentennial of the French Revolution to the upheaval in Eastern and South-Eastern Europe in the late eighties and early nineties. This revised edition in Frenchw invites us to take another look at this period of our recent European past by examining the links between revolutionary ideas and the construction of nationalisms, as the work of any historian as a rule tends to converse with the issues of their own era. This re-examination of the politics of the Enlightenment brings a new perspective, in the light of other contexts and shifts the focus by using the Balkans as a starting point. It reveals a new vision of how French revolutionary ideas were received in Europe and how that reception was criticised by liberal thinkers, as well as providing a more thorough perspective on the specific role Hellenism played in the new landscape that emerged between the end of the 18th century and the middle of the 19th century. The eminently revolutionary ideas of nationhood and freedom had a particular resonance in the Balkans and in South-Eastern Europe.